Cumulative and booster effects of tdcs sessions on drug cravings, lapse, and cognitive impairment in methamphetamine use disorder: A case study report. Issue 4 (24th May 2016) - Shariatirad, Schwann; Vaziri, Alaleh; Hassani‐Abharian, Peyman; Sharifi Fardshad, Mona; Molavi, Nader; Fitzgerald, Paul B
Abstract : Background and Objectives: Transcranial Direct Current Stimulation (tDCS) is a non‐invasive brain stimulation method, which shows promising therapeutic effects in controlling drug cravings. Methods: In this study, we present cumulative and booster effects of tDCS sessions on methamphetamine cravings, lapse, and cognitive impairment in a methamphetamine dependent subject. Results: Our study shows cumulative effects of continuous anodal tDCS sessions on right dorsolateral prefrontal cortex (DLPFC) could reduce drug cravings and their consequences. Discussion and Conclusions: Moreover, booster tDCS treatments might be helpful in controlling psychological stress and drug cravings. (Am J Addict 2016;25:264–266)